Preparation of Rotenone Derivatives and in Vitro Analysis of Their Antimalarial, Antileishmanial and Selective Cytotoxic Activities (2014)
ABSTRACT: Six derivatives of the known biopesticide rotenone were prepared by several chemical transformations. Rotenone and its derivatives showed differential in vitro antiparasitic activity and selective cytotoxicity. In general, compounds were more active against Plasmodium falciparum than Leishmania panamensis. Rotenone had an EC50 of 19.0 µM against P. falciparum, and 127.2 µM against L. panamensis. Although chemical transformation does not improve its biological profile against P. falciparum, three of its derivatives showed a significant level of action within an adequate range of activity with EC50 values < 50.0 µM. This antiplasmodial activity was not due to red blood cell hemolysis, since LC50 was >>400 µM. On the other hand, all derivatives displayed a non-specific cytotoxicity on several cell lines and primary human cell cultures.